Effect of intracoronary administration of AAV1/SERCA2a on ventricular remodelling in patients with advanced systolic heart failure: results from the AGENT‐HF randomized phase 2 trial. (10th April 2017) - Hulot, Jean‐Sébastien; Salem, Joe‐Elie; Redheuil, Alban; Collet, Jean‐Philippe; Varnous, Shaida; Jourdain, Patrick; Logeart, Damien; Gandjbakhch, Estelle; Bernard, Claude; Hatem, Stéphane N.; Isnard, Richard; Cluzel, Philippe; et al.
Abstract: Aims: Restoration of sarco/endoplasmic reticulum Ca 2+ ATPase (SERCA2a) activity through gene transfer improved cardiac function in experimental and pilot studies in humans with heart failure. The AGENT‐HF (NCT01966887) trial investigated the impact of adeno‐associated virus (AAV1)/SERCA2a on ventricular remodelling using multimodality non‐invasive cardiac imaging. Methods and results: AGENT‐HF was a single centre, randomized, double‐blind, placebo‐controlled trial in adult patients with NYHA class III–IV ischaemic or non‐ischaemic heart failure and left ventricular ejection fraction ≤35%. Eligible patients were randomized to receive a single intracoronary infusion of either 1 × 10 13 DNase‐resistant particles of AAV1/SERCA2a or placebo. The primary endpoint was change in left ventricular end‐systolic volume (LVESV), measured by cardiac computed tomography at 6 month follow‐up. We planned to include 40 patients but the trial was terminated prematurely as the sponsor suspended further enrolment following neutral results of the CUPID‐2 outcome trial. At the time of termination, nine patients were randomized with five patients infused with AAV1/SERCA2a and four with placebo. At 6 months, LVESV was increased in both groups compared with baseline: median (interquartile range) in AAV1/SERCA2a vs. placebo: 13 (13;14) mL vs. 3.5 (−36;36) mL, P = 0.74, with a mean difference between groups of 11.4 mL in favour of placebo. No safety issues were noted. Conclusion: AGENT‐HF failed to demonstrate any improvement in ventricular remodelling in response to AAV1/SERCA2a at the dose studied. However, because of premature termination, the study was underpowered to demonstrate an effect of AAV1/SERCA2a and these data should be interpreted with caution.